Evaluation of the antifungal effect and adhesive strength of a denture adhesive supplemented with nystatin - Alvim , Graziele Cristina; Beatriz da Silva , Camilla Beatriz da; Oliveira, Viviane de Cássia; Reis, Andréa Cândido dos; Watanabe, Evandro; Penazzo Lepri, César Penazzo; Castro, Denise Tornavoi de (Revista Prevenção de Infecção e Saúde, 2024)
Introduction: The scientific basis related to the effect of incorporating antifungals on the properties of denture adhesives is scarce. This study incorporated an antifungal agent into an adhesive and evaluated the influence on biofilm formation and adhesive strength. Design: Specimens in resin based on polymethylmethacrylate (PMMA) were divided into groups: PMMA (No Adhesive); PMMA+Ultra Corega Cream Adhesive and PMMA+Ultra Corega Cream Adhesive+Nystatin. Biofilm of Candida albicans was grown on the specimens and the cell viability was investigated by counting colony forming units (CFU/mL). Adhesive strength was tested after 5 minutes, 6 and 12 hours. For microbiological analysis, data were evaluated by Kruskal-Wallis and Dunn’s post test, and for analysis of adhesive strength by two-way ANOVA and Bonferroni post test (α=.05). Results: There was a reduction in biofilm formation on the surface of the nystatin-modified adhesive (p<.001). After 5 minutes, the adhesive strength of the modified Ultra Corega Cream was greater than that of the commercial product (p=.048), with no significant difference in the other times (p>.05). Implications: The incorporation of nystatin on denture adhesive reduced biofilm accumulation, with a positive influence on the initial adhesive strength, it may be a viable alternative for delivering the drug to the patient.